Kinematics Simulation Analysis of the Non-coaxial Style Two-output Impulse Generating Mechanism based on ADAMS - Gu Wen; Du Li; Feng Jun; Chen Kui; Wei Dong (Jixie chuandong)
In order to reduce the pulsation of output angler velocity of the non-coaxial style of two-output impulse generating mechanism,by using rigid body dynamics software ADAMS for parametric modeling,and combining the MATLAB for data analysis,the variation law of the double output rod angular speed and acceleration and the institutional average,pulsation coefficient and abrupt change of angular acceleration with crank length change are obtained.Through the simulation analysis of example,the consistency of output motion and the crank speed adjustability are verified,and the variation law of the mechanism pulsation will be decrease with the increase of crank length.Finally,the impact of long-rod OE and EF change on the double output motion law of mechanism is analyzed,it is shows that,after increasing the length of the rod OE and EF,the mechanism pulsation decreased,a theoretical basis of the dimension synthesis and optimization of the impulse generating mechanism is provided.